Last leaf on the tree [compact disc] - Nelson, Willie, 1933- (Legacy Recordings, 2024)
Now, for his 76th studio album and 153rd album overall as he celebrates his 91st year, Willie Nelson turns his gaze to a collection of songs by rock legends, idiosyncratic singer-songwriters, alt-rock heroes, and indie folk artists. The result is a gorgeously cohesive rumination on loss, love, and world-weary hope, perfectly complemented by spare and spooky musical production.